Physiotherapy Management Condition of Low Back Pain Lumbar Spondylosis Using Transcutaneous Electrical Nerve Stimulation and William Flexion Exercise Modalities at Pku Muhammadiyah Gamping Hospital - Febriadi, Fandi (Research of Service Administration Health and Sains Healthys, 2020)
Low Back Pain is pain that is felt in the lower back region, can be a local pain, and radicular pain or both. Pain originating from the lower back can refer to other regions or otherwise derived from other areas in the felt in the lower back area, then do a treatment of physiotherapy by using modalities of physiotherapy in the form Transcutaneus Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and William's Flexion therapy. Objective: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion (LGS), and reduction of muscle spasm in conditions of Low Back Pain. Therapy: modalities used in the case of Low Back Pain are Transcutaneous Electrical Nerve Stimulation (TENS), Short Wave Diathermy (SWD), and William's Flexion Exercise Therapy. Results: The results obtained after the conducted therapy 6 times with modalities SWD, TENS, and Therapeutic Exercise William's Flexion are as follows: pain silent T1 = 0 mm to T6 = 0 mm, tenderness T1 = 60 mm to T6 = 30 mm , pain motion T1 = 20 mm to T6 = 0 mm, LGS Trunk Flexion T1 = 6 cm into T6 = 7 cm, LGS extension Trunk T1 = 2 cm into T6 = 2 cm, muscle spasm Paravertebra T1 = 2 to T6 = 0. Conclusion: SWD, TENS, and William's Flexion Exercise therapy can reduce motion tenderness and pain, improve LGS, and reduce muscle spasm in conditions of Low Back Pain.